Identification of novel strategies to radiosensitise tumour cells - Anbalagan, S (2014)
In this study we found that tumour cells can be radiosensitised by targeting the DNA damage response kinases, ATM and ATR. Furthermore, we highlight that Wee1 inhibitors, which are already under the clinical trials need to be further investigated in combination with radiation in the context of tumour hypoxia. In addition, we observed that induction of autophagy using STF-62247 can lead to radiosensitisation of VHL deficient RCC cells. Our studies with the rapamycin analogue temsirolimus, already in the clinic for the treatment of various cancers, can be a potential candidate as a radiosensitiser for RCC cells. Overall, these finding led us to investigate further whether autophagy inducing compounds, which are either in clinic or in clinical trials, can effect the response to radiation. From a panel of candidate drugs which are known to induce autophagy we identified an aminopeptidase inhibitor, CHR-2797. CHR-2797 induces autophagy in the oesophageal cancer cell lines FLO-1 and OE21. Although, our results with CHR-2797 demonstrate it as a potential radiosensitiser, the mechanism of its radiosensitisation needs to be established. Our results from CHR-2797-induced radiosensitisation, further led us to investigate if other aminopeptidase inhibitors have a role in radiosensitisation. Therefore, we selectively screened candidate aminopeptidase inhibitors and identified some promising effects on radiosensitivity.